RIP140 in thyroid hormone-repression and chromatin remodeling of Crabp1 gene during adipocyte differentiation - Park, Sung Wook (Oxford University Press, 2009)
Cellular retinoic acid binding protein 1 (Crabp1) gene is biphasically (proliferation versus differentiation) regulated by thyroid hormone (T3) in 3T3-L1 cells. This study examines T3-repression of Crabp1 gene during adipocyte differentiation. T3 repression of Crabp1 requires receptor interacting protein 140 (RIP140). During differentiation, the juxtaposed chromatin configuration of Crabp1 promoter with its upstream region is maintained, but the 6-nucleosomes spanning thyroid hormone response element to transcription initiation site slide bi-directionally, with the third nucleosome remaining at the same position throughout differentiation. On the basal promoter, RIP140 replaces coactivators GRIP1 and PCAF and forms a repressive complex with CtBP1, HDAC3 and G9a. Initially active chromatin marks on this promoter, histone modifications H3-Ac and H3K4-me3, are weakened whereas repressive chromatin marks, H3K9-me3 and H3K27-me3 modification and recruitment of G9a, HP1α, HP1γ and H1, are intensified. This is the first study to examine chromatin remodeling, during the phase of hormone repression, of a bi-directionally regulated hormone target gene, and provides evidence for a functional role of RIP140 in chromatin remodeling to repress hormone target gene expression.